PENGARUH KECERDASAN EMOSIONAL, IKLIM ORGANISASI DAN STRES KERJA TERHADAP KINERJA PEGAWAI (Studi Kasus di Kantor Pusat Badan SAR Nasional Jakarta) - Irwan Zalukhu (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: This study was conducted to determine the effect of emotional intelligence,organizational climate and job stress on employee performance. The population in thisstudy were employees at the Head Office of National SAR Agency (BASARNAS)Jakarta. Sampling was done by metore accidental sampling. The method used in thisstudy is a descriptive analysis of the data collection through literature review,observation, interview. Analysis was conducted on the validity, reliability test, theclassic assumption test, correlation and regression testing. Results of the analysisshowed that emotional intelligence is partially significant effect on employeeperformance is strongly correlated with empathy Dimension initiative. Partial results ofthe analysis of organizational climate have a significant effect on employeeperformance. Dimensional support strongly associated with cooperation. Partial resultsof the analysis of job stress had no effect on employee performance. Results ofsimultaneous analysis of emotional intelligence and organizational climate have asignificant effect on employee performance.Keywords: Emotional Intelligence, Organizational Climate, Job Stress, EmployeePerformance